Um modelo de aferição de usabilidade de web sites, orientados ao usuário idoso - Costa, Marcelo Santana (2013)
In order to present a method to assess the usability of web site targeted at elderly users, the approach presented in this paper is intended to verification from the user perspective using the old method of investigation, combined with the prospect of experts, using the method of inspection. The measurement from the point of view of the user is based on the study of the public to which the site is directed, considering the level of the user in the use of web resources and their profile as their needs in order to be able to establish the requirements for measuring usability more appropriate. The gauging specialists turn, is based inspection methods in order to verify compliance with a set of rules of usability of web sites geared to elderly users. The method presented in this paper provides a systematic and orderly assessment of usability as well as validation of the results obtained for the methods used. Finally, to support measurement methodology presented measurements are developed based on the expectations and desires of elderly users, attending the course of introduction to computer science Extension Project - UNCISATI - University of the Third Age University of Health Sciences Alagoas - UNCISAL.